An Effective Numerical Method for Singularly Perturbed Nonlocal Boundary Value Problem on Bakhvalov Mesh - Arslan, Derya (Journal of Informatics and Mathematical Sciences, 2019)
The present study focuses on obtaining an absolutely accurate computational solution of a linear singularly perturbed problem with integral boundary condition on Bakhvalov mesh. A finite difference scheme was constructed and the approximation of the presented problem was obtained. Based on the \(ε\)-perturbation parameter, it was established that the first-order uniform convergence was within the discrete maximum norm. A numerical experiment was performed in order to demonstrate the effectiveness and accuracy of the presented method. The results were confirmed through the relevant table and figures.